Studi Evaluatif Profesionalisme Guru Lulusan S1 PGSD dalam Keterampilan Menulis - Loliyana Loliyana; Fitria Akhyar (Universitas Lampung, 2020)
The teacher must be able to present good language ethical learning. It considers that the teacher is not only a source of learning material but also as a role model for students. Therefore, this study was conducted to describe the teacher's writing skills. This study used a descriptive analytic approach using a questionnaire and portfolio documentation. The research sample consisted of 26 teachers in Bandar Lampung. Based on research data, the average value of writing skills was 74.12. Thus, it can be concluded that the language skills of elementary school teachers in Bandar Lampung City are categorized as good.Keywords: Writing skills, teacher. DOI: http://dx.doi.org/10.23960/jiip.v2i1.21792